2023
DOI: 10.1101/2023.01.24.525403
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microsaccades are directed towards the midpoint between targets in a variably cued attention task

Abstract: Reliable, non-invasive biomarkers that reveal the internal state of a subject are an invaluable tool for neurological diagnoses. Small fixational eye movements, called microsaccades, are a candidate biomarker thought to reflect a subject's focus of attention (1, 2). The linkage between the direction of microsaccades and attention has mainly been demonstrated using explicit and unambiguous attentional cues. However, the natural world is seldom predictable and rarely provides unambiguous information. Thus, a use… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Saccade preparation is another factor which can modulate the low-frequency oscillations in V4 (Steinmetz and Moore, 2014) that might contribute to better behavioral discriminability. However, a recent study which used the same experimental data found no difference in the microsaccade direction -a potential indicator of saccade preparation (Hafed and Krauzlis, 2012) -between hits and miss trials (Willett and Mayo, 2023).…”
Section: Shared and Distinct Effects Of Attention And Behavior On Lfpmentioning
confidence: 85%
“…Saccade preparation is another factor which can modulate the low-frequency oscillations in V4 (Steinmetz and Moore, 2014) that might contribute to better behavioral discriminability. However, a recent study which used the same experimental data found no difference in the microsaccade direction -a potential indicator of saccade preparation (Hafed and Krauzlis, 2012) -between hits and miss trials (Willett and Mayo, 2023).…”
Section: Shared and Distinct Effects Of Attention And Behavior On Lfpmentioning
confidence: 85%